Neutrophils Recruited by NKX2‐1 Suppression via Activation of CXCLs/CXCR2 Axis Promote Lung Adenocarcinoma Progression - Anita S La'ah; Ping‐Hsing Tsai; Aliaksandr A. Yarmishyn; Lo‐Jei Ching; Chih‐Ying Chen; Yueh Chien; Jerry Chieh‐Yu Chen; Ming‐Long Tsai; Yi‐Chen Chen; Chun Ma; Po‐Kuei Hsu; Yung‐Hung Luo; et al. (Advanced Science)
Abstract NK2 Homeobox 1 (NKX2‐1) is a well‐characterized pathological marker that delineates lung adenocarcinoma (LUAD) progression. The advancement of LUAD is influenced by the immune tumor microenvironment through paracrine signaling. However, the involvement of NKX2‐1 in modeling the tumor immune microenvironment is still unclear. Here, the downregulation of NKX2‐1 is observed in high‐grade LUAD. Meanwhile, single‐cell RNA sequencing and Visium in situ capturing profiling revealed the recruitment and infiltration of neutrophils in orthotopic syngeneic tumors exhibiting strong cell‐cell communication through the activation of CXCLs/CXCR2 signaling. The depletion of NKX2‐1 triggered the expression and secretion of CXCL1, CXCL2, CXCL3, and CXCL5 in LUAD cells. Chemokine secretion is analyzed by chemokine array and validated by qRT‐PCR. ATAC‐seq revealed the restrictive regulation of NKX2‐1 on the promoters of CXCL1, CXCL2, and CXCL5 genes. This phenomenon led to increased tumor growth, and conversely, tumor growth decreased when inhibited by the CXCR2 antagonist SB225002. This study unveils how NKX2‐1 modulates the infiltration of tumor‐promoting neutrophils by inhibiting CXCLs/CXCR2‐dependent mechanisms. Hence, targeting CXCR2 in NKX2‐1‐low tumors is a potential antitumor therapy that may improve LUAD patient outcomes.